The influence of 2-propanol and acetone on oviposition rate and oviposition site preference for acetic acid and ethanol of Drosophila melanogaster. - Eisses, K.T. (Behavior Genetics, 1997)
Drosophila melanogaster strains, homozygous for the alcohol dehydrogenase alleles AdhF, AdhS, and Adhn4 respectively, were tested for oviposition site preference with a Multiple Choice Device consisting of 18 patches per choice disk. Equal numbers of patches with ethanol-, acetic acid-, and water-supplemented medium were offered simultaneously. Patches with acetic acid-supplemented medium were chosen predominantly as oviposition sites. Pretreatment of flies with increasing concentrations of 2-propanol to inhibit alcohol dehydrogenase (ADH) activity resulted not only in a decreasing choice of acetic acid patches, but also in the laying of a decreasing number of eggs. Adh-null mutant flies showed a similar change in behavior pattern after 2-propanol treatment. Therefore it was concluded that ADH activity is not involved primarily in oviposition site preference behavior. A complicating factor is acetone, the oxidation product of 2-propanol, which had an even larger impact on egg production. However, differences in ADH allozymes with respect to biochemical oxidation capacity of secondary alcohols will not necessarily lead to differences between the Adh genotypes in oviposition rates or apparent changes in preferences, due to additional biochemical differences in inhibition rates by acetone of the various allozymes and other enzyme systems.